DESIGN OF SCRATCH-BASED ALPHA WORD GAME TO IMPROVE STUDENTS’ VOCABULARY AT PRIMARY SCHOOL - Hidayat, Anwarul; Hasanudin, Cahyo; Fitrianingsih, Ayu; Taufiqur Rohmah, Ima Isnaini (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
Scratch as a website which could be utilized by beginners to create learning media such as educational game. This study aimed to improve students’ vocabulary at primary school using scratch-based educational game. The method of his study was SDLC waterfall model. Results of this study showed that the design of Alpha Word game was arranged in the stages of requirement analysis, design, implementation, testing, and maintenance. Alpha Word was a game that was designed to improve students’ vocabulary by utilizing attractive and simple visual.